Disruptive Behavior in the Postdisciplinary Society - Gaete-Silva, Joaquin; Gaete, Alfredo (Frontiers in Psychology, 2021)
Responding to disruptive behavior has become increasingly problematic in current Westernized societies, impacting people’s well-being globally. In the context of the current Special Issue, in this article we advance the concept of problematic disruptive behavior (PDB) as a suitable “window” to better understand some aspects of the deep interdependence of social participation, citizenship, justice, and well-being. To do so, we also advance the notion of postdisciplinary society to account both for the apparent rise of problematic disruptive experiences, and the increased social conflict within which such experiences get often entangled. More specifically, we argue that formerly morally acceptable responses to problematic disruption, such as punishment and discipline, have lost social legitimacy and, to that extent, they aggravate the problems they were intended to resolve. We provide a genealogical account of the surge of such postdisciplinary order with a focus on the moral transition on ideas of justice, of personal entitlements, and authority. We conclude outlining an alternative way to respond to disruptive behaviors that we anticipate will be both more effective and acceptable in the current postdisciplinarian milieu.